Campur Kode dalam Film "Ketika Cinta Bertasbih" - Ummu Fatimah Ria Lestari (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Ketika Cinta Bertasbih film is a religious cinema. This film tells about an Al Azhar student named Khairul Azzam, his family in Indonesia and his friend in Cairo. As code mixing is defined as all cases where lexical items and grammatical features from two languanges appear in one sentence, the writer concludes that the characters uses code mixing in their communication. As a study of sociolinguistics, this paper explains on code mixing used by Azzam and his friends who come from all etnics. They had mixed their Indonesian with Javanese, Indonesian and Arabic, Indonesian and English. It is found that the strategy of code mixing mostly used in the drama is insertion.